Effect of HA Nanoparticles on Adsorption of Vitamin D3 on Super-Hydrophobic PA6 Nanofibrous Scaffold - Esfahani,Hamid (2020)
ABSTRACT Vitamin D3 has significant roles in bone growth and the prevention of osteoporotic fractures. The present study investigated the effect of hydroxyapatite nanoparticles decoration onto polyamide-6 nanofibrous scaffold on adsorption behaviour of Vitamin D3. To synthesize the nanofibrous scaffold, an electrospinning device was used, and the surface of the scaffold was characterized by scanning electron microscopy, energy dispersive spectrometry, Fourier transform infrared spectroscopy, and measurement of the water contact angle. The antibacterial activity test against E. coli and S. aureus bacteria indicated no such activity of pristine and hydroxyapatite decorated scaffold. The results demonstrated that a hydrophobic and high porous scaffold was formed, and hydroxyapatite nanoparticles were distributed inside the polyamide-6 nanofibers homogenously. Results showed that the hydroxyapatite nanoparticles improved the adsorption efficiency of polyamide-6 scaffold. It was found that the amount of adsorbed Vitamin D3 molecules onto the polyamide-6/HA scaffold was rapid during the first hour of immersion (24.4 ng.cm-3), then declined over the next 3 h, and eventually reached a stable percentage of about 10.3 ng.cm-3. This phenomenon appears to be related to the high adsorption potential of porosities and the hydrophobic nanofibers during the first stage of immersion and non-occupied hydroxyapatite ceramic sites during the final stage of immersion.